AKTIVITAS ANTIPIRETIK KOMBINASI EKSTRAK ETANOLMENIRAN (Phyllanthus niruriL) DAN DAUN BELIMBING WULUH (Avverhoabillimbi) PADA TIKUS PUTIH JANTAN YANG DIINDUKSI VAKSIN DPT-Hb - Yuli Wahyu Tri Mulyani; Annisa Mulia Anasis; Vatiyah Hari Utami (JFL : Jurnal Farmasi Lampung, 2022)
Abstract Fever is defined as a change in the body's temperature regulation mechanism which results in an increase in body temperature above normal above 32.7ÂºC. Antipyretics are drugs used to reduce fever, one of which is paracetamol, but the use of paracetamol in large doses and for a long time has the potential to cause damage to the kidneys, brain, liver (hepatotoxic), disorders of the digestive system, respiratory system and hematological effects. These unwanted effects can be minimized using the active ingredients of meniran (Phylantus niruri L) and wuluh (Avverhoa bilimbi) plants. The purpose of this study was to prove the antipyretic activity of the combination of meniran leaf extract (Phylantus niruri L) and wuluh starfruit leaf (Avverhoa bilimbi) in male white rats (Rattus norvegicus L) induced by the DPT-Hb vaccine. The principle of this research is laboratory experimental research. This study included a combination of samples of meniran leaves and starfruit leaves, making thick extracts of meniran leaves and starfruit leaves, and testing the effect of antipyretics on the test animals. This study used the DPTâ€“Hb (fever) vaccine induction method and the SPSS analysis method. The results showed that ethanol extract of meniran leaves 200mg/200grBB, ethanol extract of belimbing wuluh leaves 7.2mg/200grBB and a combination of ethanolic extract of meniran leaves with starfruit at doses of 200mg/200grBB and 7.2mg/200grBB, 100mg/200grBB and 3.6mg/ 200grBW, 200mg/200grBW and 3.6mg/200grBW, 100mg/200grBW, and 7.2mg/200grBW had antipyretic effects on male white rats. Keywords: antipyretic, starfruit, meniran